A Methodology for the Evaluation of Hygrometric and Mechanical Properties of Consolidated Stones. Issue 5 (3rd July 2016) - D'Orazio, Marco; Munafò, Placido
ABSTRACT: Several authors agree that stone surface consolidation works should not significantly alter original mechanical and hygrometric properties of the stones in order to avoid differential stress between the consolidated and non-consolidated parts. Specific limitedly destructive methodologies have been developed for assessing the variation in both mechanical and hygrometric properties, but they require preliminary calibration procedures that are very costly to adopt in terms of both time and money. This research study describes an analytical and experimental procedure aimed at obtaining the necessary hygrometric and mechanical characterization of natural and/or artificial stone, before and after consolidation works, by simply assessing the variation in the distribution of the porous structure.